Stakeholder values on the management of African elephants for large tree conservation in protected areas - Robin M. Cook; Ed T. F. Witkowski; Michelle D. Henley (European Journal of Wildlife Research, 2025)
Stakeholder perspectives play a crucial role in conservation decisions, particularly for species with complex ecological and social impacts, such as African savanna elephants ( Loxodonta africana ). In a South African protected area experiencing high elephant densities and significant tree loss, we surveyed 170 stakeholders, including conservation managers, property owners, tourists, and tourism personnel. Using a Likert scale and thematic analysis, we evaluated their attitudes towards tree protection, waterhole closures, contraception, and culling to mitigate elephant impacts on large trees. Results showed strong support for waterhole closures and tree protection, particularly among younger conservation managers and property owners, who viewed these methods as effective in dispersing elephant populations and safeguarding valuable trees. Conversely, tourists and younger stakeholders preferred non-lethal strategies like contraception, while conservation managers expressed practical concerns about its feasibility. Culling emerged as the most divisive strategy, supported primarily by older and male stakeholders in conservation but largely opposed by tourists due to ethical concerns. The chord diagram illustrated distinct patterns, with conservation managers aligning more with waterhole closures and culling, while property owners and tourists favoured tree protection and contraception. These findings highlight the diversity in stakeholder values, shaped by demographic factors, and underscore the need for adaptive, context-specific management strategies. Our study provides a framework for conservation policies that balance ecological objectives with social acceptability, promoting sustainable coexistence between elephants, large trees, and diverse stakeholder interests.

Drivers of woody plant phylogenetic and taxonomic beta diversity across an urban density gradient - Justice Muvengwi; Hilton G. T. Ndagurwa; Tatenda Nyenda; Ed T. F. Witkowski; Monicah Mbiba (Urban Ecosystems, 2025)
Urban plant diversity patterns are influenced by socioeconomic factors, yet our understanding of these relationships in Global South cities remains limited. We investigated how taxonomic and phylogenetic beta diversity of woody plants vary across Harare's socioeconomic gradient, examining patterns for indigenous and exotic species. We surveyed 300 household yards across 15 suburbs representing low-, medium-, and high-density areas, characterized by differences in property values, population density, and yard size. For combined species, both taxonomic and phylogenetic beta diversity showed significant positive relationships with property value and yard area, supporting the 'luxury effect' hypothesis. However, patterns differed when analysing species groups separately. Exotic species demonstrated strong socioeconomic filtering, with greater taxonomic diversity in wealthy areas but consistently low phylogenetic turnover across suburbs, suggesting selection of evolutionarily related species. Indigenous species showed unexpected resilience in high-density areas, maintaining greater phylogenetic diversity than affluent suburbs. While species turnover dominated overall beta-diversity patterns, phylogenetic nestedness contributed substantially more than taxonomic nestedness, particularly for exotic species. These findings challenge conventional urban ecology paradigms and highlight the importance of considering both taxonomic and phylogenetic dimensions when assessing urban biodiversity. The retention of phylogenetically diverse indigenous communities in high-density areas presents opportunities for biodiversity conservation in African cities.

Sexual Dimorphism in Anthonomus santacruzi (Coleoptera: Curculionidae): a Biological Control Agent of Solanum mauritianum Scopoli (Solanaceae) - Archbold Sasa; Rafał Gosik; Ed T. F. Witkowski; Marcus J. Byrne; Miłosz A. Mazur (Neotropical Entomology, 2020)
There is evident variation in body size amongst Anthonomus santacruzi Hustache, 1924, weevils. The aims of this study were to assess if the variation in body size in A . santacruzi weevils is a result of sexual dimorphism and what features can be used to distinguish males from females. The weevils were collected from field sites in Mpumalanga, South Africa, where they were introduced as biocontrol agents of Solanum mauritianum Scopoli. Body structures and the presence/absence of the tergal notch was examined under an optical stereomicroscope and SEM to assess differences between sexes. The morphometric analysis of the body structures included rostrum length (base–apex and antennal insertion–apex), elytral length and width, pronotum length and width, first tarsus length, first tibia length, funiculus length and total body length. Rostrum length, elytra length and width and total body length were significantly larger in females than in males. A tergal notch in the 8th abdominal tergite was present in males and absent in females. The body structure; of rostrum length, elytra length and width and total body length overlapped between sexes in some specimens. The abdominal tergal notch was found to be the most useful body structure to distinguish males from females in A . santacruzi .

Impact of biocontrol agents on Lantana camara in an inland area of South Africa - Naweji Katembo; Ed T. F. Witkowski; David O. Simelane; Alan J. Urban; Marcus J. Byrne (BioControl, 2020)

Correction to: Differences between sun and shade habitats on the invasive shrub Lantana camara and its biocontrol agent Teleonemia scrupulosa - Nic Venter; Maurice Mkasi; Phuluso Mudau; Solomon W. Newete; Blair W. Cowie; Ed T. F. Witkowski; Marcus J. Byrne (Arthropod-Plant Interactions, 2020)

Differences between sun and shade habitats on the invasive shrub Lantana camara and its biocontrol agent Teleonemia scrupulosa - Nic; Maurice Mkasi; Phuluso Mudau; Solomon W. Newete; Blair W. Cowie; Ed T. F. Witkowski; Marcus J. Byrne (Arthropod-Plant Interactions, 2019)

Post-release evaluation of a combination of biocontrol agents on Crofton weed: testing extrapolation of greenhouse results to field conditions - Lisa Buccellato; Marcus J. Byrne; Jolene T. Fisher; Ed T. F. Witkowski (BioControl, 2019)

A review of Solanum mauritianum biocontrol: prospects, promise and problems: a way forward for South Africa and globally - Blair W. Cowie; Nic Venter; Ed T. F. Witkowski; Marcus J. Byrne; Terence Olckers (BioControl, 2018)

Planning for the Maintenance of Floristic Diversity in the Face of Land Cover and Climate Change - Debbie Jewitt; Peter S. Goodman; Barend F. N. Erasmus; Timothy G. O’Connor; Ed T. F. Witkowski (Environmental Management, 2017)

Mapping landscape beta diversity of plants across KwaZulu-Natal, South Africa, for aiding conservation planning - Debbie Jewitt; Peter S. Goodman; Timothy G. O’Connor; Barend F. N. Erasmus; Ed T. F. Witkowski (Biodiversity and Conservation, 2016)

Crunchtime: sub-Saharan stinkbugs, a dry season delicacy and cash cow for impoverished rural communities - Cathy M. Dzerefos; Ed T. F. Witkowski (Food Security, 2015)

Fruits of our labour: contribution of commercial baobab (Adansonia digitata L.) fruit harvesting to the livelihoods of marginalized people in northern Venda, South Africa - Sarah M. Venter; Ed. T. F. Witkowski (Agroforestry Systems, 2013)

Are environmental factors important facilitators of pompom weed (Campuloclinium macrocephalum) invasion in South African rangelands? - Jeremy Goodall; Ed T. F. Witkowski; Craig D. Morris; Lesley Henderson (Biological Invasions, 2011)

Does allelopathy explain the invasiveness of Campuloclinium macrocephalum (pompom weed) in the South African grassland biome? - Jeremy Goodall; Ed T. F. Witkowski; Sigrun Ammann; Carl Reinhardt (Biological Invasions, 2010)

The South African Experience of Conservation and Social Forestry Outreach Nurseries - Jenny Botha; ED T. F. Witkowski; Jacklyn Cock (Environmental Management, 2006)

A Landscape Ecological Approach to Address Scaling Problems in Conservation Management and Monitoring - MARC STALMANS; KEVIN BALKWILL; ED T. F. WITKOWSKI; KEVIN H. ROGERS (Environmental Management, 2001)